2015
DOI: 10.1038/nplants.2015.140
|View full text |Cite
|
Sign up to set email alerts
|

An RLP23–SOBIR1–BAK1 complex mediates NLP-triggered immunity

Abstract: Plants and animals employ innate immune systems to cope with microbial infection. Pattern-triggered immunity relies on the recognition of microbe-derived patterns by pattern recognition receptors (PRRs). Necrosis and ethylene-inducing peptide 1-like proteins (NLPs) constitute plant immunogenic patterns that are unique, as these proteins are produced by multiple prokaryotic (bacterial) and eukaryotic (fungal, oomycete) species. Here we show that the leucine-rich repeat receptor protein (LRR-RP) RLP23 binds in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
509
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 399 publications
(526 citation statements)
references
References 53 publications
13
509
0
4
Order By: Relevance
“…6B; Grefen and Blatt, 2012a). This ratiometric BiFC system has been utilized successfully by a number of different laboratories with a diverse range of PPIs (Karnik et al, 2013b;Lipka et al, 2014;Albert et al, 2015;Kumar et al, 2015;Le et al, 2016;Perrella et al, 2016).…”
Section: Construct Designmentioning
confidence: 99%
See 1 more Smart Citation
“…6B; Grefen and Blatt, 2012a). This ratiometric BiFC system has been utilized successfully by a number of different laboratories with a diverse range of PPIs (Karnik et al, 2013b;Lipka et al, 2014;Albert et al, 2015;Kumar et al, 2015;Le et al, 2016;Perrella et al, 2016).…”
Section: Construct Designmentioning
confidence: 99%
“…Additionally, an interaction in CoIP could be due to the presence of a protein complex of multiple interactors, with an apparent binary interaction facilitated by known or unknown cofactors (Hall, 2005). This comes as a blessing in disguise, as it allows higher order protein complexes or ligand-induced dimerization to be dissected, a phenomenon that is neatly exploited when an interaction between two POIs is either induced by an exogenously applied factor (ligand, pathogen, and so on) or disrupted in a knockout line of the endogenous bridging factor (Chinchilla et al, 2007;Albert et al, 2015;Fuchs et al, 2016) Recently, two novel techniques have been developed that circumvent the limitations of traditional CoIP. Both developments, single-molecule pull down (Jain et al, 2011) and real-time single-molecule CoIP (Lee et al, 2013), use total internal reflection microscopy (Axelrod, 2001) to detect interactions on a coverslip.…”
Section: In Planta Coip: One To Bind and One To Findmentioning
confidence: 99%
“…It has been demonstrated that SOBIR1 physically interacted with Cf-4, Ve1, LepR3, Rlm2, AtRLP1, AtRLP23, AtRLP30 and AtRLP42, and was required for the proper function of these RLPs. 9,10,12,13,15,16,[24][25][26] However, it is unclear about the biological relevance of the physical interaction between SOBIR1 and two developmental RLPs CLV2 and TMM, respectively. It could postulate that SOBIR1 may involve in the CLV2-and/or TMM-mediated developmental processes.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Although the biological functions of most AtRLP genes still remain unknown, a number of AtRLP genes have been assigned functions. In addition to CLV2 and TMM, the functionally characterized AtRLP proteins comprise AtRLP1/ReMAX that mediates recognition of eMAX, 13 AtRLP3/RFO that involves in resistance to the vascular wilt fungus Fusarium oxysporum, 14 AtRLP23 that perceives a conserved fragment present in most necrosis and ethyleneinducing peptide (NEP) 1-like proteins and subsequently activate the immunity, 15 AtRLP30 that implicates in resistance against Pseudomonas syringae pv. phaseolicola, 12 AtRLP42/ RBPG1 that confers resistance to endopolygalacturonases, 16 AtRLP44 that activates brassinosteroid signaling through interaction BAK1, 17 and AtRLP51/SNC2 and AtRLP55 that implicate in basal defense against the bacterial pathogen Pseudomonas syringae pv tomato DC3000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation